Compound strengthening and dynamic characteristics of laser-induced double bubbles. (May 2019) - Tong, Yanqun; Wang, Chao; Yuan, Shouqi; Han, Kuiguo; Chen, Xiaoming; Yang, Ning; Ren, Xudong
Highlights: A better compound strengthening performance of double cavitation bubbles in water and on material surface is investigated. The dynamic characteristics of laser-induced double bubbles are described. The relations between distance parameter H and strengthening performance of double bubbles are discussed. Abstract: As a result of controllability, the new laser-induced bubbles strengthening technology has seen rapid development in recent years. Apart from bubbles observed in water and on a material surface, single-pulsed lasers induce double bubbles. The dynamic characteristics of double bubbles were investigated using a high-speed camera. The residual stress and the surface morphology were measured to evaluate the strengthening effect. The compound strengthening mechanism of double bubbles with high temperature and high pressure was discussed. The results show that the transient characteristics of double bubbles in water and on the surface of the material are different, such as the pulsation period and the size, although the two bubbles are induced at the same time. And the strengthening performance of double bubbles depends on the distance between the focus point of the laser and the material surface. This study provides a practical strengthening method based on double bubbles induced by nanosecond pulsed laser.